Usability Evaluation on Website E-Fishery using Heuristic Evaluation - Sauzan Salsabila Azzahra; Maihuhatul Mar'ah; Tiara Maharani (Jurnal Mandiri IT, 2022)
PT. Multidaya Teknologi Nusantara is a company that produces technology that can automatically feed fish which can be monitored through the eFishery website. A website must include aspects in order to maintain the information available in it and the quality of use. Problems that are often encountered in a website are usability problems which result in users often being mistaken for an inappropriate interface. Since it was founded in 2013, there has never been a usability evaluation of the eFishery website so it is not known whether this website is in accordance with what the community needs or not. Based on these problems, usability assessment needs to be carried out using a heuristic method on the efishery.com website based on suggestions and criticisms from several evaluators who are experts in the field of web programming, UI/UX. The goal is to find out problems with usability on the efishery.com website and as a consideration for the efishery.com website development team for further improvements to suit user needs. This study focuses on the usability assessment of the efishery.com website along with recommended solutions. The method used in this research is Heuristic which involves three experienced experts as evaluators to assess the efishery.com website. From the results of this study, it was found that the problem with the highest percentage was on the principle of esthetics and Minimalist Design with the heuristic code H7 was 46% while the lowest percentage was in the code H2, H3, H4 and H5 of 0%, so it does not have to be repaired.